Avoidance in bowtie systems - Grannell, Michael J. (Ars mathematica contemporanea, 2022)
There are ten configurations of two bowties that can arise in a bowtie system. The avoidance spectrum for three of these was determined in a previous paper M. J. Grannell et al., Aequationes Math. 85, No. 3, 347--358 (2013). In this paper the avoidance spectrum for a further five configurations is determined.
Keywords: avoidance; bowtie system; configuration; izogibanje; konfiguracija; sistem metuljčkov; Steiner triple system; Steinerjev sistem trojk